Value creation in international business. Volume 2, - Marinova, Svetla Trifonova; Larimo, Jorma; Nummela, Niina (Palgrave Macmillan, 2016)
The edited collection brings into focus the meanings, interpretations and the process of value creation in international business. Exploring value creation in the context of emerging and developed economies, Volume 2 takes the perspective of small and medium sized enterprises and examines various approaches to value creation in the process of firm internationalization. Providing theoretical and practical insights, the authors open an intellectual debate into what value is, and how it is created through the internationalization activities of firms. Value Creation in International Business is a pioneering two volume work intended to provoke theoretical and empirical development in International Business research. Moreover, it is intended as a bridge between concepts derived from general business firm-level research agendas such as value creation and business model, and internationalization approaches and activities of firms. .
Keywords: International business enterprises.; elektronické knihy; electronic books